(untitled) (Orinoquia, 2009)
I would like to initiate this document by making a brief description of the term Biotechnology, hoping to not hurt the feelings of many other professionals better versed than I, on the details of this science, as the application of traditional and/or scientific knowledge to manipulate microorganisms, cells or even higher organisms, directed to supply goods and services to the daily growing human population. With almost 30-year-old, biotechnology, driven by the ability to transplant a gene from one organism into another to introduce novel functionality in the receiving organism, has evolved to repro- gram cellular behavior or incorporate increasingly com- plex biosynthetic pathways (to produce novel metabolic products or to achieve greater system integration) or genetic regulatory constructs (to modulate the activity of recombinant genes in space and time) (Bhalerao, 2009). Biotechnology one of the riskiest industries has achieved a dynamic growth and unparalleled discovery, outstanding advances and contributions to human and animal medicine. This has mainly been possible throughout the exploration of diverse unicellular and multicellular genomes, the genes and the proteins they encode, and together with the development of dozens of technologies, reach every day a better understand- ing of cell biology, homeostasis and disease. Thus, biotechnology has established as an industry, where any bio-product can be patentable.